2022
DOI: 10.2147/ijgm.s295859
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Associated Neurocognitive Disorder (HAND): Obstacles to Early Neuropsychological Diagnosis

Abstract: Despite the recent advances in HIV treatment, HIV-associated neurocognitive disorder (HAND) prevalence remains high, especially in the mild forms. Current recommendations endorse routine screening for HAND and early identification, but there are several obstacles in diagnosing and managing cognitive impairment in people living with HIV. The purpose of this review is to provide an overview of the concepts and diagnostic tools in the field of HAND and report on the strengths and limitations of currently availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 82 publications
1
10
0
1
Order By: Relevance
“…Despite recent advances in managing and treating infected individuals, HIV-associated neurocognitive disorders (HAND) were reported in between 30 and 60% of adults [ 2 , 3 , 4 , 5 , 6 , 7 ]. Epidemiological studies report that HIV-associated dementia (HAD) is rare nowadays (2–4%) [ 7 ], and most PLWH present mild forms of cognitive dysfunction, including asymptomatic neurocognitive impairment (ANI) and mild neurocognitive disorder (MND) [ 4 , 8 , 9 ]. A systematic review of the literature reported a pooled prevalence rate for HAD, according to the Frascati criteria of 5% (95% CI 3.5–6.8) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent advances in managing and treating infected individuals, HIV-associated neurocognitive disorders (HAND) were reported in between 30 and 60% of adults [ 2 , 3 , 4 , 5 , 6 , 7 ]. Epidemiological studies report that HIV-associated dementia (HAD) is rare nowadays (2–4%) [ 7 ], and most PLWH present mild forms of cognitive dysfunction, including asymptomatic neurocognitive impairment (ANI) and mild neurocognitive disorder (MND) [ 4 , 8 , 9 ]. A systematic review of the literature reported a pooled prevalence rate for HAD, according to the Frascati criteria of 5% (95% CI 3.5–6.8) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of cART in 1996 was a landmark in HIV history, as effective this antiretroviral treatment decreased the severity of neurological impairments. Although the frequency of HAND did not decrease, with an unchanged prevalence of cognitive impairment in PLWH with systemic viral suppression, dementia is rare, while the milder, non-demented forms of HAND account for most cases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of people suffering from HAND has remained unchanged before and after the ART era (~20–30%), but the severity of the neurocognitive impairments has diminished from HIV-associated encephalopathy (HIVE) or dementia (HAD) to the predominance of less severe asymptomatic neurocognitive impairment (ANI) and mild neurocognitive disorder (MND) phenotypes [ 4 , 16 , 30 , 31 , 32 ]. The diagnosis of HAND relies on neuropsychological testing and functional status assessments [ 4 , 33 ] although the presence of comorbidities such as age-related cognitive decline and related systemic diseases as well as the improved recognition of pre-existing mental disorders make the diagnosis of MND and ANI increasingly challenging [ 34 , 35 ]. Moreover, the determinants or a reliable diagnostic biomarker for HAND and the mechanisms underpinning HIV persistence in the brain, together with the impact of this reservoir on the brain’s microenvironment, remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to accurately diagnose ANI at present. Diagnosis requires a series of neurocognitive scale tests, which are time-consuming, and the results are easily affected by various factors, such as the patient's education level, environment, and examiner ( 9 , 10 ). In addition, these patients have no obvious clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%